Kak_delajut_porsu - Kovylin; Maksimova; Filchenko; Kuznetsova; Karelin
The languages of the collection, Eastern Khanty and Southern Selkup, (i) are severely endangered: each numbers under 20 last proficient speakers; (ii) have existing legacy data in Tomsk with limited access, which is to be improved as a result of the project; (iii) are characterized by areal contact contiguity; (iv) are ethnographically consistent, with the last traditional culture practitioners. The cooperative proposal between the University of Zurich and Tomsk State Pedagogical University builds on extended research experience with the respective languages, and relevant documentation methodology. The proposal pursues documentation and analysis of two endangered languages of Western Siberia, Russia in order to gain insight into local processes of area formation. How to make porsa fish flour. Архив ЯНС ТГПУ. Том С 27. стр. 36-37. born in Karelino of Verkhne-Ketskij district, the family of a hunter, moved to Alipka in 1930s, passed 4 years of school in Maksimkin Yar, 1936-1937 attended school in Vertikos of Kargasok district - graduated 7 grades. 1937-1939 studied in teacher training college in Kolpashevo. 1939-1948 served in Red Army at the Soviet-Turkish border. 1946-1948 lived in Orlovka, served as village council head. From 1948 lived in Ust'-Ozernoe.